Kajian Yuridis Tanda Tangan Elektronik Sebagai Alat Bukti yang Sah dalam Perspektif Hukum Acara Perdata - Nasrul Nasrul (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
The aim of this research is to determine the position and legal strength of electronic signatures as evidence. And to find out the resolution of civil disputes submitted by the parties using electronic document evidence signed with an electronic signature. The type of research used is Normative Juridical. The research results show that the recognition and legal force of electronic signatures as electronic documents in Indonesian evidentiary law is recognized for its essence after being regulated in the applicable laws and regulations. The resolution of civil disputes submitted by the parties using electronic document evidence signed with an electronic signature to resolve disputes resulting from non-fulfillment of agreements agreed upon by the electronic transaction actors, can be resolved through a lawsuit to the court, or through non-litigation institutions such as arbitration. , mediation, negotiation, in accordance with the agreement for resolving disputes due to non-fulfillment of the achievements agreed upon by both parties, in general resolving disputes regarding violations of the agreement, electronic transaction actors prefer to resolve disputes through non-litigation, because it is relatively cheaper, and the cost is not too expensive.